Transport of Zn (II) by TDDA-Polypropylene Supported Liquid Membranes and Recovery from Waste Discharge Liquor of Galvanizing Plant of Zn (II). (2nd November 2017) - Ur Rehman, Hanif; Akhtar, Gul; Ur Rashid, Haroon; Ali, Nauman; Ahmad, Imtiaz; Ur Rehman, Saeed; Khan, Kamin; Arshad, Muhammad
Abstract : The facilitated passage of Zn (II) across flat sheet supported liquid membrane saturated with TDDA (tri-n-dodecylamine) in xylene membrane phase has been investigated. The effect of acid and metal ion concentration in the feed solution, the carrier concentration in membrane phase, stripping agent concentration in stripping phase, and coions on the extraction of Zn (II) was investigated. The stoichiometry of the extracted species, that is, complex, was investigated on slope analysis method and it was found that the complex (LH)2 ·Zn(Cl2 ) is responsible for transport of Zn (II). A mathematical model was developed for transport of Zn (II), and the predicted results strongly agree with experimental ones. The mechanism of transport was determined by coupled coion transport mechanism with H + and Cl − coupled ions. The optimized SLM was effectively used for elimination of Zn (II) from waste discharge liquor of galvanizing plant of Zn (II).